Spatial proximity and how to shape it: An empirical case study of selected German technology parks - Elena Schlich (Spatial transformation: Processes, strategies, research design, 2022)
The three interrelated factors of knowledge, learning and innovation are regarded as the key components of the knowledge economy (OECD 1996). In the past decades, attempts have been made to describe the systematic impact and correlation of these three factors by means of various concepts in connection with innovation theory. The spatial proximity of the respective bearers of knowledge in relation to each other was initially identified as an important aspect of the innovation process. Yet spatial proximity alone is not enough. Its innovation-promoting effects can only be realised in combination with other forms of proximity and physical spatial design features. Through this understanding of the underlying innovation theory, it was hoped that it would be possible to influence the innovation process, a possibility that is of particular importance for economic policy in connection with the construction of local knowledge infrastructures. Technology parks (TPs) bear witness to how insights into innovation theory have evolved. Hence, this article briefly outlines the development of the TP concept and examines the innovation-promoting effects it generates through the specific way in which it shapes spatial proximity. As illustrated by three case studies, the TP concept is adaptable to the innovation-promoting needs of organisations based on site. However, the analyses show that not all the measures and instruments actually benefit on-site knowledge networking as an innovationpromoting activity.
urn:nbn:de:0156-08910876; hdl:10419/251347; https://econpapers.repec.org/RePEc:zbw:arlfob:19
Keywords: 710; Innovation process; knowledge; spatial proximity; knowledge transfer; technology parks